XÁC ĐỊNH CHUYỂN DỊCH HIỆN ĐẠI ĐỚI ĐỨT GÃY SÔNG HỒNG THEO SỐ LIỆU LƯỚI GPS TAM ĐẢO - BA VÌ (1994 - 2007) - Hải, Vy Quốc; Tô, Trần Đình; Liêm, Ngô Văn (Vietnam Journal of Earth Sciences, 2012)
Determination of present crustal movements of Red River Fault Zone by the TamDao - BaVi GPS network (1994-2007) The Tam Dao - Ba Vi GPS network was established for investigation of present crustal movements of Red River Fault Zone. Five GPS measurement campaigns were carried out in 1994, 1996, 1998, 2000, 2006-2007 by Trimble 4000 SSE/SSi with Compact L1/L2 W/G antennas. GPS data were processed by GPSurvey 2.35 and Bernese 4.2 softwares. The results show that, in 1994-2007 time duration, the movements of Red River Fault Zone was small, with the rate of about 1±0,3mm/year.